2018
DOI: 10.1007/s00520-018-4183-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a genetic and a psychological factor as correlates of anxiety, depression, and chronic stress in men with prostate cancer

Abstract: Each of these two factors may provide valuable information regarding the vulnerability of PCa patients to anxiety, depression, or chronic stress. Suggestions are made for their inclusion in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…regarding the former of these associations in PCa patients, 4,18,19 there is little evidence of the latter effect. Investigation of both of these associations represents a relatively new field of enquiry in the PCa field that has the potential to contribute to the development of individualised resilience training when needed by these men.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…regarding the former of these associations in PCa patients, 4,18,19 there is little evidence of the latter effect. Investigation of both of these associations represents a relatively new field of enquiry in the PCa field that has the potential to contribute to the development of individualised resilience training when needed by these men.…”
Section: Introductionmentioning
confidence: 97%
“…Although between 14% 1 and 27% 2 of prostate cancer (PCa) patients report being depressed, due at least in part from the stress of diagnosis and treatment for PCa, 3 there is evidence that psychological resilience (PR) can ‘buffer’ the association between stress and depression in these men 4–7 . The association between stress and PR itself may also be of interest because Rutter 8–10 suggested that experiencing adverse events could actually increase later resilience, an effect that he referred to as ‘steeling’ (p. 337) 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depression and anxiety are considered emotional symptoms that together may provide a multifaceted description of the psychological distress experienced by PC patients (SHARPLEY et al, 2018). Moreover, the surgical treatment of PC is usually influenced by the onset of these symptoms, especially when they are related to surgical side effects such as extended hospitalization periods, pain, sexual dysfunction and urinary incontinence (PASTORE et al, 2018).…”
Section: Introductionmentioning
confidence: 99%